Blue ocean strategy : how to create uncontested market space and make the competition irrelevant - Kim, W. Chan.; Mauborgne, Renée. (Boston Harvard Business School Publishing Corporation, 2015)
This book presents a systematic approach to making the competition irrelevant and outlines principles and tools any organization can use to create and capture their own blue oceans. The expanded edition includes two new chapters and expanded third one.
Includes bibliographical references and index.
osa 10/01/2019, ijb,28/01/2019
Loans
Keywords: New products; Market segmentation